Penguatan Pendidikan Karakter Bangsa Bagi Generasi Milenial - Qurban Hajar; Swandi (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
This article describes the Strengthening of Character Education for Millennials. The rapid development of technology provides a variety of positive benefits and also negative impacts on life, especially for the younger generation today or often called the millennial generation. The millennial generation is a generation that in their life can not be separated from the name of technology. Millennials make information technology a lifestyle or lifestyle. Millennials are very vulnerable to problems that occur in social media because in this generation most of their time is spent surfing the internet. Therefore, the development of technology in the digital era requires a strong controller to be able to choose foreign values ​​and cultures that enter Indonesia, one of them being through education. The importance of national character-based education for the current millennium generation in order to equip individuals to compete in the millennial era. Character or personality will be the controller for individuals using good technology and information in accordance with its benefits. So that a lot of culture and information from outside who enter Indonesia will be filtered well without making excessive negative impacts on the millennial generation.